THE WAVE OF MILLENNIAL MUSLIM SHARIA LIFESTYLE AS AN OPPORTUNITY FOR SOREANG ISLAMIC SHARIA HOUSING - ENDAH CHRISTIANINGSIH (PT. Anagata Sembagi Education, 2025)
As we've seen since early 2018, Bandung has become a hub for Islamic studies, popular among teenagers and adults aged 19 to 40, often referred to as the millennial generation. This social phenomenon emerged like a massive wave, bringing millennials, especially from Bandung and its surrounding areas, to enjoy the beauty of this social phenomenon. The ghiroh, or enthusiasm for seeking knowledge from monotheism to Islamic jurisprudence, has raised awareness among Bandung's youth to apply Islamic values in all aspects of their lives. This study aims to determine how the opportunities that arise from this social phenomenon for the Sharia Islamic Soreang (SIS) housing where the concept offered by SIS is an integrated Islamic residence with the tagline sakinah from home which researchers believe will be a special attraction for the Muslim millennial generation. The method in this study uses a descriptive qualitative method, namely a method that describes the situation based on existing facts with data obtained through interviews with key informants, direct and indirect observations and documentation. As for the selection of key informants, researchers classified them based on their roles in management and consumers based on age. The integrated Islamic housing concept promoted by Perumahan Sharia Islamic Soreang is considered a suitable choice for millennial Muslims, thus automatically presenting an opportunity for SIS. However, currently, management has not focused on seriously addressing this market potential. The gap between product prices and millennial Muslim purchasing power is acutely felt, necessitating a specific strategy to maximize this opportunity.